Erectile dysfunction and cardiovascular risk factors in a Mediterranean diet cohort. Issue 1 (27th January 2016) - Ramírez, R.; Pedro‐Botet, J.; García, M.; Corbella, E.; Merino, J.; Zambón, D.; Corbella, X.; Pintó, X.; ,
Abstract: Background: Erectile dysfunction affects more than 100 million men worldwide, with a wide variability in prevalence. An overall association of cardiovascular risk factors, lifestyle and diet in the context of ED in a Mediterranean population is lacking. Aim: To assess ED prevalence and associated factors in a Mediterranean cohort of non‐diabetic patients with cardiovascular risk factors. Methods: Observational, cross‐sectional study of patients aged over 40 treated at cardiovascular risk units in Catalonia. Anthropometric data, risk factors, lifestyle and diet habits were recorded. ED was assessed using the International Index of Erectile Function. Results: Four hundred and forty patients included, 186 (42.3%) with ED (24.8% mild, 6.8% moderate and 10.7% severe). ED presence and severity were associated with age, obesity, waist circumference, hypertension, antihypertensive treatment and ischaemic disease. Patients with ED were more frequently smokers, sedentary and consumed more alcohol. In multivariate analysis, consumption of nuts (> twice a week) (OR 0.41 (95% CI 0.25 to 0.67) and vegetables (≥ once a day) (OR 0.47 (95% CI 0.28–0, 77)), were inversely related to ED. Obesity (as BMI ≥ 30 kg/m 2 ) (OR 2.49 (95% CI 1.48–4.17)), ischaemic disease (OR 2.30 (95% CI 1.22 to 4.33), alcohol consumption (alcohol‐units a day) (OR 1.14 (95% CI 1.04 to 1.26), and age (year) (OR = 1.07 (95% CI 1.04–1.10) were directly related to ED. Conclusion: Erectile dysfunction is a common disorder in patients treated in lipid units in Catalonia for cardiovascular risk factors. This condition is associated with age, obesity, ischaemic disease and unhealthy lifestyle habits.